Differential Diagnosis of Acute Abdomen - Pereira, Miguel Paiva (2020)
We present a case of a 12-year-old male, complaining of a 4-hour course of abdominal pain, progressively worsening in the left iliac fossa irradiating to the hypogastric and ipsilateral inguinal regions, without improvement despite acetaminophen therapy. No fever, vomiting or diarrhea was noticed. Past medical history was positive for a pattern of constipation with hard stools and sometimes traces of blood. On examination, pain facies, position of defense to palpation in the left iliac fossa and pain to decompression. Inguinoscrotal region examination was normal. Blood analyses showed no leukocytosis, neutrophilia or CRP elevation. Abdominal ultrasound revealed an oval hyperechoic lesion, compatible with edematous fat, surrounded by a thin layer of fluid, at the transition of the descending to the sigmoid colon, corresponding to the tenderness point. Those images were in keep with epiploic appendagitis. The patient was discharged home with oral anti-inflammatory medications for 5 days and acetaminophen as needed. Epiploic appendagitis is a benign and self-limiting condition caused by an ischemic infarction due to torsion or spontaneous thrombosis of the epiploic appendage central vein. It occurs most commonly in the second to fifth decades of life. The incidence is unknown but has been reported in 2-7% of patients suspected of having diverticulitis and in 0.3-1% of patients suspected of having appendicitis.(1) These conditions are usually and definitely diagnosed with computer tomography (CT) in adult patients. In young patients, regarding the radiation hazard of CT, it may be imaged solely by ultrasound.(2) The ultrasound findings include an incompressible oval hyperechoic image (fat), surrounded by a thin layer hypoechoic fluid and tender at probe compression. Treatment should be conservative with anti-inflammatories and analgesics.(3,4) Complete resolution usually occurs between 3-14 days. Surgery should be reserved for refractory cases with symptoms persistence or worsening or presence of complications.(5)